My Life in the Wild : Elephant - Costain, Meredith; Illustrated by Hanna, JGary (Sydney, N.S.W Weldon Owen, 2012)
Pictures and text show how different animals use posture, plumage, or other natural decoration to warn, elude, or engage in courtship.
Includes Index, Glossary and Colred Illustrations.
Animal Planet (Television Network)
Keywords: Animals -- Habits and behavior